Acquired heterotopic ossification of the temporomandibular joint. Issue 12 (December 2017) - Mercuri, L.G.; Saltzman, B.M.
Abstract: Although the risk factors and diagnosis of heterotopic ossification (HO) are discussed in the orthopedics literature, the etiology of HO, as well as its prevention and management, remain theoretical. Furthermore, there is a lack of information in the literature regarding HO in temporomandibular joint replacement (TMJR). This article provides a qualitative review of information relative to the etiology, diagnosis, and management of HO to inform and encourage further investigation in TMJR. The orthopedic HO literature considered for this qualitative review was drawn from a comprehensive examination of the subject published previously by one of the authors. Using the key words "heterotopic ossification" or "heterotopic bone", citations in the PubMed database from both the dental and oral and maxillofacial surgery literature were reviewed. Based on this, it appears that the etiology, diagnosis, imaging, laboratory testing, risk factors, prophylaxis, and non-surgical and surgical options available for the management of TMJR-related HO are similar to those for orthopedic HO, but further elucidation is required for TMJR. There is a lack of published information in the literature on TMJR. Therefore, using the literature from this review as a foundation, studies should be developed and reported so that alloplastic TMJ surgeons have evidence-based protocols that will lead to the early detection and potential prevention of HO.